2011
DOI: 10.1109/titb.2011.2160272
|View full text |Cite
|
Sign up to set email alerts
|

Toward Synergy-Based Brain-Machine Interfaces

Abstract: This paper demonstrates a synergy-based brain-machine interface that uses low-dimensional command signals to control a high dimensional virtual hand. First, temporal postural synergies were extracted from the angular velocities of finger joints of five healthy subjects when they performed hand movements that were similar to activities of daily living. Two synergies inspired from the extracted synergies, namely, two-finger pinch and whole-hand grasp, were used in real-time brain control, where a virtual hand wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
27
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(28 citation statements)
references
References 25 publications
1
27
0
Order By: Relevance
“…Also shown in the figure are the hand postures of the reconstructed movement across time. Adapted from Vinjamuri et al (2011) on the principles of data reduction and dimensionality reduction, are soon to find place in tele-surgery and tele-robotics ( Vinjamuri et al (2007)). Synergies are projected to be miniature windows to provide immense help in next generation rehabilitation.…”
Section: Applications Of Synergiesmentioning
confidence: 99%
See 2 more Smart Citations
“…Also shown in the figure are the hand postures of the reconstructed movement across time. Adapted from Vinjamuri et al (2011) on the principles of data reduction and dimensionality reduction, are soon to find place in tele-surgery and tele-robotics ( Vinjamuri et al (2007)). Synergies are projected to be miniature windows to provide immense help in next generation rehabilitation.…”
Section: Applications Of Synergiesmentioning
confidence: 99%
“…Synergies are projected to be miniature windows to provide immense help in next generation rehabilitation. Recently our group has demonstrated a synergy based brain machine interface where two control signals calculated from the spectral powers of the brain signals controlled two synergies, that commanded a 10 DoF virtual hand ( Vinjamuri et al (2011)). This showed promising results for controlling a synergy-based neural prosthesis.…”
Section: Applications Of Synergiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Additionally, Vidaurre et al demonstrated EEG-based control of an exoskeleton [38]. Invasive brain-computer interfaces have demonstrated accurate and real-time control of advanced prosthetics such as modular prosthetic limb [15,23,40,41].…”
Section: Introductionmentioning
confidence: 99%
“…It is thus an important target for brain-machine interfaces (BMIs) being developed for patients with impaired limb function due to neurological lesions of motor pathways (e.g., spinal cord injury, amyotrophic lateral sclerosis, stroke, etc.). Recent work has demonstrated that grasp types [1], grasp timing [2], hand postures [3], and reach parameters [4] can be decoded from spectral changes in human intracranial electroencephalographic (iEEG) signals, and that movement-related spectral modulation of iEEG can be used for online control of BMIs, for example during dexterous grasping [5], when selecting between grasp types and elbow movement [6], or for three dimensional cursor control [7]. We therefore sought to determine whether human iEEG could be used to provide simultaneous and independent online control of reaching and grasping movements, thus demonstrating segregation of these two movement types at the spatial scale of iEEG macroelectrodes.…”
Section: Introductionmentioning
confidence: 99%